Dissociation of tetramethylsilane for the growth of SiC nanocrystals by atmospheric pressure microplasma. Issue 5 (2nd March 2020) - Haq, Atta Ul; Lucke, Philip; Benedikt, Jan; Maguire, Paul; Mariotti, Davide
Abstract: We report on mass spectrometry of residual gases after dissociation of tetramethylsilane (TMS) during the synthesis of silicon carbide (SiC) nanocrystals (NCs) by an atmospheric pressure microplasma. We use these results to provide details that can contribute to the understanding of the formation mechanisms of NCs. Mass spectrometry reveals the presence of high‐mass polymerization products supporting the key role of neutral fragments and limited atomization. On this basis, we found that the loss of methyl groups from TMS, together with hydrogen abstraction, represents important paths leading to nucleation and growth. The combination of TMS concentration and NC residence time controls the NC mean size and the corresponding distributions. For higher precursor concentrations, the reaction kinetics is sufficiently fast to promote coalescence. Abstract : The formation mechanism of silicon carbide (SiC) nanocrystals (NCs) in atmospheric pressure plasma was investigated using the residual gas analysis of the dissociated tetramethylsilane by mass spectrometry. It was revealed that the SiC NCs are formed due to polymerization reaction. The presence of polymerization products higher than the TMS supported the main role of neutrals with limited atomization.